Obesity and hyperlipidaemia in adult males in a Semi-urban community in Jordan - Al boqai, Omar; Ali, Khalid Eltom; Abuirmelleh, Naji (Gezira Journal of Health Sciences, 2003)
Objective:   To describe the relationship between obesity and hyperlipidaemia. Methods: Cluster sampling technique-probability of households from Sareeh area. A total of 400 apparently healthy adult males aged 30-50 years were invited to participate in the study, of whom 306 completed the study. A pilot tested interview questionnaire was designed in the study to collect  the dietary history. Height, weight, waist circumference, triglycerides (TRIG) and total cholesterol (CHOL) were measured.  Obesity was categorized into three groups as indicated by BMI-C based on WHO (1997) for generalized obesity and for classifications of central obesity using waist circumference categories based on (Lean et al, 1995). Results: The means of plasma triglycerides and total cholesterol increased significantly with increasing levels of waist circumference and BMI categories (P<0.05).  There was an increase in the prevalence rates (PRs) of hypertriglyceridaemia and hypercholesterolaemia with increasing levels of obesity and its duration. The proportion ratios of hypertriglyceridaemia and hypercholesterolaemia for subjects with high and moderate obesity levels compared with subjects with normal levels were (10.1-11.6) and (6.7 -8.1) times respectively; whereas for subjects with duration of overweight>20 years compared with subjects with duration of obesity <10 years ranged (2.11-2.96) times.  Also odds ratios (ORs) of hypertriglyceridaemia and hypercholesterolaemia after controlling for confounded factors were increased with increasing levels of obesity and its duration, the highest (OR) in high obesity levels ranged (11.59-19.18, 95% CI, P<0.001) whereas for duration of obesity >20 years ranged (16.78-20.94, 95% CI, P<0.001). Central obesity had a potential risk on hypertriglyceridaemia and hypercholesterolaemia more than generalized obesity.  Conclusions: amount of body fat, location and duration are the major risk factors on hyper- trigly ceridaemia and hypercholesterolaemia which emphasizes the need for concentrated e-ffort  to prevent and treat obesity rather than just any associated co-morbidities.